(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The genetic variation and differentiation among different populations of sheep in Bangladesh were studied by using 18 microsatellite markers. A total of 140 samples- 37 from Bangladesh Central (BGC), 40 from Bangladesh East (BGE), 39 from Bangladesh North (BGN) and 24 from Garole (GAR) were genotyped. The allele number per locus ranged from 2 to 10. The average number of alleles per population was 5.50 ± 1.72, 5.33 ± 2.00, 6.39 ± 2.06 and 4.72 ± 1.71 for BGC, BGE, BGN and GAR respectively. Heterozygosity was found in the range from 0.5084±0.0187 (BGE) to 0.5810±0.0237 (GAR). The genetic distance (DA) between BGN and GAR was the highest (0.1071) and that between BGC and BGN was the lowest (0.0664). In the phylogenetic dendrogram, BGC and BGN grouped in the same cluster, while BGE and GAR formed another two separate clusters. The results indicate that all four sheep populations had rich genetic diversity and the Garole sheep (GAR) is considered as an independent breed in Bangladesh. Keywords: Sheep; Microsatellite marker; Genetic relation; Phylogenetic dendrogram DOI: 10.3329/jbau.v7i2.4736 J. Bangladesh Agril. Univ. 7(2): 291-294, 2009